Volumetric Optical Strain Mapping Technique for Strain Measurement in Monolithic Silica Aerogel Nanocomposites - Ma, Allen. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Mechanical Engineering.; Advisors: Stephen III Steiner, and Jeffrey Guasto.; Committee: Richard Henshaw, and Marc Hodes.; Keyword: Mechanical engineering.; Aerogels are a diverse class of high-porosity solid-phase nanostructured materials that exhibit a wide range of extreme materials properties, such as low bulk density and low thermal conductivity. Aerogel products can be made in various form factors, with the most common commercial form factors being blankets and particles. Aerogel monoliths (i.e., shaped 3D aerogel forms) offer unique opportunities for applications such as insulating windows and polymer aerogel products that can be machined into complex shapes without collapsing. However, monoliths can crack, deform, or otherwise undergo mechanical failure during supercritical drying, requiring overly conservative and thus time-consuming and expensive processes to achieve usable parts. The mechanisms for such failure are not fully understood, as they could possibly be due to solvent-solid interactions or nonuniform strain states. It is necessary to be able to make in situ strain measurements during the drying process to understand these failure mechanisms. Volumetric optical strain mapping during supercritical drying is a promising method for measuring strain in real time. Here, we develop a technique for strain mapping by utilizing photon upconversion fluorescent particles and mapping the fluorescence intensity of upconversion nanoparticles to the strain state of the drying gel. To demonstrate this capability, we first establish the ability to illuminate a voxel within an aerogel with infrared lasers. The voxel is used as an optical probe for interrogating a given location within the monolith. A silica aerogel nanocomposite is embedded with inorganic NaYF4:Yb/Er upconversion nanoparticles (UCNPs). We demonstrated the feasibility of utilizing UCNPs for volumetric strain mapping in ex situ analysis, and with modification to the technique there is promise for in situ applications.